Rehabilitation for Gait Restoration Using Functional Electrical Stimulation - Rika Wahyuni Arsianti; Achmad Arifin (Fidelity : Jurnal Teknik Elektro, 2023)
Functional Electrical Stimulation (FES) is used to assist paralyzed patients in restoring their ability to move due to damage to the central nervous system, spinal cord injury or stroke. FES delivers electrical pulses to nerve or muscle tissue to activate the muscles to move. The human musculoskeletal system has different responses between subjects and changes in muscle characteristics from time to time during electrical stimulation. Fuzzy controller is used to overcome the problem of nonlinearity of the muscle system. The purpose of this study is to restore the ability to knee joint extension movement using FES. The results show that achieving the target extension angle can be achieved and is able to cope with different subject responses.